PENGARUH PENGGUNAAN AI DAN LITERASI DIGITAL TERHADAP KEMANDIRIAN BELAJAR MAHASISWA PENDIDIKAN AKUNTANSI DENGAN EFIKASI DIRI SEBAGAI MEDIASI - Gibran Regusta Ade Prabowo; Ita Nuryana (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of the use of Artificial Intelligence (AI) and digital literacy on student learning independence with self-efficacy as a mediating variable. The study used a quantitative explanatory approach on 327 Accounting Education students of Semarang State University, class of 2023 and 2024, with a sample of 180 students selected using proportional stratified random sampling technique. Data were collected through questionnaires and analyzed using SEM-PLS. The results showed that the use of AI had a positive and significant effect on learning independence (t = 2.533; p = 0.011), but did not affect self-efficacy (t = 1.693; p = 0.090). Digital literacy did not directly affect learning independence (t = 1.930; p = 0.054), but had a positive effect on self-efficacy (t = 5.183; p = 0.000). Self-efficacy had a positive effect on learning independence (t = 3.152; p = 0.002). Self-efficacy did not mediate the relationship between AI use and learning independence, but it did mediate the relationship between digital literacy and learning independence (t = 2.664; p = 0.008). The novelty of this study lies in examining the role of self-efficacy in the relationship between AI use, digital literacy, and students' learning independence. Findings indicate that AI use directly enhances learning independence, while digital literacy enhances it through self-efficacy.